Effect of High Strain Rates on Adiabatic Shear Bands Evolution and Mechanical Performance of Dual-Phase Ti Alloy - Hao, Fang; Du, Yuxuan; Wang, William Yi; Mao, Youchuan; Yin, Junlei; Zou, Chengxiong; Chen, Haisheng; Wang, Kaixuan; Feng, Yong; Liu, Xianghong; Li, Jinshan (Frontiers in Materials, 2022)
In the present work, the adiabatic shear characteristics of our recent designed α+β dual-phase Ti alloy at different strain rates have been investigated by hat shaped specimen. The deformation process is divided into three stages: the work hardening stage, steady stage and unstable thermal softening stage. Along or near the shear deformation paths, the microvoids and the cracks can be captured at the strain rate of 1.8 × 104 s-1, 2.0 × 104 s-1, and 2.3 × 104 s-1, both of which contribute to the stable and unstable softening. It is found that dynamic stored energy of cold work will be significantly improved by the enhanced high strain rate. In the view of coupling analysis of inverse pole figure and grain boundary map, it seems like that low angle grain boundaries present a good resistance to the formation of cracks and the thermal softening. On the contrary, high angles grain boundaries are typically located in ASBs and their affecting regions, which is in line with the reported results. While the geometrical necessary dislocation (GND) density of adiabatic shear band (ASB) and its surroundings increased significantly, the width of the ASB becomes wider as the strain rate increases, which is consistent with the theory of sub-grain rotation dynamic recrystallization model. The formation of multiple ASBs in the corner position is schematically illustrated and the average elastic modulus and hardness of the ASB region are lower than the α and β phases, combined with the GND analysis, which proves that the ASB is a thermal softening zone in this experiment.